N-Total, Serapan N, dan Pertumbuhan Kacang Tanah (Arachis hypogaea L.) Akibat Inokulasi Azotobacter dan Bahan Organik pada Tailing Tambang Emas Pulau Buru, Maluku - Febby Nur Indriani; Reginawanti Hindersah; Pudjawati Suryatmana (Fakultas Pertanian Universitas Padjadjaran, 2017)
Mining may directly affect the surrounding environment if the tailings produced were not processed properly. Tailings from gold mining activities caused critical land condition both physically and chemically. The damage of environment caused by mining activities need to rehabilitated. Rehabilitation can be done through revegetation of pioneer plants, addition of organic matter, and potential microbiological applications. This research was conducted to determine the potential of organic matter and Azotobacte inoculant for gold mine tailing rehabilitation on soil total N, N uptake, and growth of peanut. Experiment was carried out at Biology Laboratory, Soil Fertility and Plant Nutrition Laboratory Department of Soil Science and Land Resources and Greenhouse of Faculty of Agriculture, Universitas Padjadjaran, Jatinangor. The experimental design was Split Plot consisted of three replications. Main plot is dosages of organic matter consisted of 1,5%, 3% and 4,5% dosages, sub plot was the species of Azotobacter and consisted of control, indigenous Azotobacter sp., Azotobacter chroococcum, indigenous Azotobacter sp. and Azotobacter chroococcum constria. The result showed there was no interaction between Azotobacter sp. inoculant and organic matter toward total N, N uptake, and growth of peanut on tailing. Organic matter of 1,5% and 3% significantly increased total N of soil.Keywords: Azotobacter, nitrogen, peanut, tailing